1996
DOI: 10.1210/en.137.5.1599
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic activity is involved in changes in intrafollicular insulin- like growth factor-binding protein levels during growth and atresia of ovine ovarian follicles

Abstract: In the sheep, follicular growth is characterized by both an increase and a decrease in the level of intrafollicular insulin-like growth factor-binding protein-3 (IGFBP-3) and IGFBPs less than 40 kDa (IGFBP-2, -4, and -5), respectively. In contrast, follicular atresia is associated with a decrease and a large increase in levels of IGFBP-3 and IGFBPs less than 40 kDa, respectively. To assess whether intrafollicular proteases are involved in such changes, follicular fluid from follicles of different sizes and deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
2

Year Published

1996
1996
2008
2008

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 0 publications
3
41
2
Order By: Relevance
“…In other species, these changes in IGFBP-2 levels with follicular health status were shown to be related to both changes in mRNA expression (sheep [67], pigs [65,66]) and in proteolytic degradation (sheep [68], pigs [69]). …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In other species, these changes in IGFBP-2 levels with follicular health status were shown to be related to both changes in mRNA expression (sheep [67], pigs [65,66]) and in proteolytic degradation (sheep [68], pigs [69]). …”
Section: Discussionmentioning
confidence: 96%
“…-~~~~* --·-and/or to change in proteolytic degradation (humans [70], sheep [68], pigs [69]). The precise role for the various IGFBPs in follicular function remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Western ligand blots were quantified using the same image analysis system (see above) and as previously described [3,8]. The amount of radiolabeled IGF-II bound to the 35-kDa IGFBP-2, 30-kDa IGFBP-5, and 24-kDa IGFBP-4 was estimated from the ratio of the IOD (integrated optical density in arbitrary units) of these bands in the sample to that of the 35-30-kDa bands in a follicular fluid from bovine atretic follicle run simultaneously on each ligand blot and taken as internal standard.…”
Section: Quantitative Analysismentioning
confidence: 99%
“…Local paracrine processes are likely responsible for such changes in level of intrafollicular IGFBPs < 40 kDa observed during follicular growth and atresia. Particularly, in the sheep, we have recently shown that ovine follicular growth in vivo is characterized by a marked increase in intrafollicular proteolytic activity degrading IGFBP-4 and to a lesser extent IGFBP-2 and -5 [8]. Follicular atresia, in contrast, is characterized by a decrease in intrafollicular IGFBP-4 and -5 proteolytic activity [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation